Detection of molecular markers linked to Ry genes in potato germplasm for marker-assisted selection for extreme resistance to PVY in AAFC’s potato breeding program - Nie, X.; Lalany, F.; Dickison, V.; Wilson, D.; Singh, M.; Koeyer, D. de; Murphy, A. (Canadian Science Publishing, 2016)
Molecular markers reported to be linked to extreme resistance (ER) against Potato virus Y (PVY) were evaluated in potato germplasm. YES3-3A and YES3-3B, markers linked to Rysto, were detected in ‘Barbara’ and its three descendants that exhibit ER to PVY; RYSC3, a marker linked to Ryadg, was detected in breeding clones NY121 and NY123. Assessment of RYSC3 as a marker for selection for Ryadg-mediated ER validated its efficacy in identification of selections with ER to PVY.